Revitalisasi Pembelajaran Interaktif: Workshop Pengembangan Sumber Belajar Adaptif Berbasis AI untuk Guru SMA Negeri 1 Sungai Penuh: (Revitalizing Interactive Learning: A Workshop on Developing AI-Based Adaptive Learning Resources for Teachers at Senior High School 1 Sungai Penuh City) - Pratama, Robin; Saudagar, Ferdiaz (Laboratorium Pembelajaran FKIP Universitas Jambi, 2025)
This community service aims to improve the capacity of teachers in utilizing artificial intelligence (AI) technology in learning at SMA Negeri 1 Sungai Penuh. Through a three-day workshop, teachers were trained to understand the concept of AI and how to use it in developing adaptive learning resources. The methods used included providing theoretical materials, practical training, and group discussions to understand the challenges and solutions to implementing AI in schools. The results of the activity showed an increase in teachers' understanding of the benefits of AI in education, as well as increased skills in integrating the technology into the learning process. However, there are still challenges such as limited infrastructure and technical skills that require further assistance. This activity succeeded in equipping teachers with basic knowledge and practical skills related to the application of AI in learning. It is recommended that there be a continuous mentoring program and improvement of technology facilities in schools to support the optimal implementation of AI. Abstrak. Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas guru dalam memanfaatkan teknologi kecerdasan buatan (AI) dalam pembelajaran di SMA Negeri 1 Sungai Penuh. Melalui workshop yang diadakan selama tiga hari, para guru dilatih untuk memahami konsep AI dan cara penggunaannya dalam mengembangkan sumber belajar adaptif. Metode yang digunakan meliputi pemberian materi teoritis, pelatihan praktis, serta diskusi kelompok untuk memahami tantangan dan solusi implementasi AI di sekolah. Hasil kegiatan menunjukkan peningkatan pemahaman guru tentang manfaat AI dalam pendidikan, serta peningkatan keterampilan dalam mengintegrasikan teknologi tersebut ke dalam proses pembelajaran. Namun, masih terdapat tantangan seperti keterbatasan infrastruktur dan keterampilan teknis yang memerlukan pendampingan lebih lanjut. Kegiatan ini berhasil membekali guru dengan pengetahuan dasar dan keterampilan praktis terkait penerapan AI dalam pembelajaran. Disarankan adanya program pendampingan berkelanjutan serta peningkatan fasilitas teknologi di sekolah untuk mendukung penerapan AI secara optimal.